Imaging-based frequency mapping for cochlear implants – Evaluated using a daily randomized controlled trial - Lambriks, Lars; van Hoof, Marc; Debruyne, Joke; Janssen, Miranda; Chalupper, Josef; van der Heijden, Kiki; Hof, Janny; Hellingman, Katja; Devocht, Elke; George, Erwin (Frontiers in Neuroscience, 2023)
Background Due to variation in electrode design, insertion depth and cochlear morphology, patients with a cochlear implant (CI) often have to adapt to a substantial mismatch between the characteristic response frequencies of cochlear neurons and the stimulus frequencies assigned to electrode contacts. We introduce an imaging-based fitting intervention, which aimed to reduce frequency-to-place mismatch by aligning frequency mapping with the tonotopic position of electrodes. Results were evaluated in a novel trial set-up where subjects crossed over between intervention and control using a daily within-patient randomized approach, immediately from the start of CI rehabilitation. Methods Fourteen adult participants were included in this single-blinded, daily randomized clinical trial. Based on a fusion of pre-operative imaging and a post-operative cone beam CT scan (CBCT), mapping of electrical input was aligned to natural place-pitch arrangement in the individual cochlea. That is, adjustments to the CI’s frequency allocation table were made so electrical stimulation of frequencies matched as closely as possible with corresponding acoustic locations in the cochlea. For a period of three months, starting at first fit, a scheme was implemented whereby the blinded subject crossed over between the experimental and standard fitting program using a daily randomized wearing schedule, and thus effectively acted as their own control. Speech outcomes (such as speech intelligibility in quiet and noise, sound quality and listening effort) were measured with both settings throughout the study period. Results On a group level, standard fitting obtained subject preference and showed superior results in all outcome measures. In contrast, two out of fourteen subjects preferred the imaging-based fitting and correspondingly had better speech understanding with this setting compared to standard fitting. Conclusion On average, cochlear implant fitting based on individual tonotopy did not elicit higher speech intelligibility but variability in individual results strengthen the potential for individualized frequency fitting. The novel trial design proved to be a suitable method for evaluation of experimental interventions in a prospective trial setup with cochlear implants.